Analisis Kelayakan Finansial Budidaya Melon pada Rumah Kaca di Kota Denpasar - THERESIA I GUSTI AGUNG BULAN; I KETUT BUDI SUSRUSA; NI MADE CLASSIA SUKENDAR (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2022)
Financial Feasibility Analysis of Greenhouse Melon Cultivation in Denpasar. Hydroponic melon cultivation in greenhouses is one of the cultivation techniques that has a great potential. The increasing demand of melons has not been accompanied by an increase in product availability. The purposes of this research are: 1) identifying the financial feasibility of hydroponic melon greenhouse cultivation in Denpasar City and (2) identifying the sensitivity level of hydroponic melon greenhouse cultivation in Denpasar City when there is an increase in input prices and a decrease in selling prices. The location was determined purposely. Primary data were obtained through interviews and secondary data were obtained through various literatures and several related agencies. The research was carried out between April and August 2020. The analysis techniques used were NPV, IRR, Net B /C, PP, and sensitivity analysis. The results of this study are: (1) the value of NPV, Net B/C, and IRR of hydroponic melon cultivation is Rp. 93.239.925, 1,97 and 24%, which means that the farming method is financially feasible because NPV> 0, IRR> interest rate and Net B/C> 1. The sensitivity of hydroponic melon cultivation occurs when the operational cost increases and the selling price decreases. It is still feasible at 15% increase of operational cost with the same selling price as well as at 15% decrease of selling price with the same operational cost, although there is a decrease of NPV value and Net B/C.